PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA GURU SEKOLAH DASAR KABUPATEN PATI - Sujiono, Endro -; -, Mulyanto - (Universitas Slamet Riyadi, 2012)
ABSTRACT This research aims to know: 1) the influence of a leadership toward the performance, 2) the influence of work discipline toward the performance, 3) the influence of a leadership toward the motivation, 4) the influence of work discipline toward the motivation, 5) the influence of motivation toward the performance. The data are collected from 55 respondents by using a census method. They are analyzed through the research instruments such as validity test by using a product moment test and the reliability test by using a cronbach alpha technique, path analysis, t test, F test and determination coefficient. The research result show that 1) the influence is positif significant of a leadership toward the performance, 2) the influence is positif significant of work discipline toward the performance. 3) the influence is positif significant of a leadership toward the motivation, 4) the influence is positif significant of the work disciplineÂ toward the job satisfaction, 5) the influence is positif significant of a job satisfaction toward the motivation, 6) the influence is not significant of a leadership toward the performance via motivation, and the influence is not significant of the work discipline toward the performance via motivation, 7) the coefficient determination shows that R Square is 0,601 or 60,1%, means that performance variable axplains is the leadership, the work discipline, and the motivation satisfaction are 60,1%, and while its remain 39,9% is explained by other variable which are not involved in regression model such as organization culture and job satisfaction. Keywords: leadership, work discipline, motivation, performance.